Hubungan Iklim Organisasi Dengan Kepuasan Kerja Karyawan di CV Primajaya Logistik Je’El Medan - Bunga Aditi; Pratiwi, Henny; Mendrofa, Syah Abadi (Jurnal Sains dan Teknologi, 2023)
This study aims to determine the relationship between organizational climate and job satisfaction at CV. Primajaya Logistic Je'El Medan Employess. Job satisfaction is the attitude or feeling of a person to view his job as a matter of being satisfied and dissatisfied, happy or unhappy that concerns a person's feelings of employees or employees for all the work they receive. This study uses a quantitative approach. The sample of this study was 45 people, the sampling technique was the total sampling method. This study uses a Likert scale model. The analysis technique used is Product Moment correlation. The results of this study indicate the rxy correlation coefficient = 0.789 with p = 0,000 (p <0.050), meaning that there is a positive relationship between organizational climate and job satisfaction. With these results, the study hypothesize in this study is that there is a positive relationship between the organizational climate and acceptable job satisfaction. The positive correlation coefficient indicates that the direction of the relationship between the two variables is positive, meaning that the higher the organizational climate, the higher job satisfaction. Organizational climate effectively contributes 69.1% on job satisfaction and 30.9% is influenced by other factors not examined in this study, such as salary factors, company characteristics etc. The empirical mean of job satisfaction variable was 128,01 while the empirical mean of organizational climate variable was 121,08, then for the hypothetical mean variable job satisfaction was 107.5 and the hypothetical mean organizational climate variable was 105. Reviewing the results of the study was declared acceptable.